Pernikahan Tanpa Persetujuan Salah Satu Pihak Dalam Perspektif Islam Dan Hukum Positif Di Indonesia - Ivan Tanoto; Andini Zelikho (al-Battar: Jurnal Pamungkas Hukum, 2025)
Some fiqh scholars are of the opinion that parents or guardians can forcibly marry their daughters, which is then known as the right of ijbar and parents who can force children to marry are called mujbir guardians. In reality, nowadays there are still parents who force their children to marry the man of their father's choice. This is not in line with Law no. 1 of 1974 concerning marriages carried out based on the consent of the prospective bride and groom. If the marriage does not have the consent of one of the parties, it can be called a forced marriage. This research is descriptive analysis which leads to normative legal research, with a research approach to legal principles. The data source was obtained from secondary data, namely by means of literature study. The data obtained was then analyzed using qualitative analysis. Based on the research results, it was found that legal certainty regarding marriage conditions related to the bride's consent when being betrothed by her guardian must exist. It turns out that the study of jurisprudence is not relevant to granting the guardian the right of ijbar to marry his daughter without the child's consent. The consequences of a marriage without the consent of the prospective bride are considered bad, because a marriage that contains an element of coercion will only bring harm to both parties (husband and wife). where according to the Law and KHI the marriage can be annulled.